HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT DEPRESI REMAJA DI LEMBAGA PEMASYARAKATAN - Lia ' Rahmawati; Arneliwati ' '; Veny ' Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   This research aimed to determine the relationship between family support and level of depression among adolescents in prison. This research used descriptive correlative method with cross-sectional approach. Samples of this research were taken using total sampling. This research’s sample consists of 46 adolescents in Lembaga Pemasyarakatan Kelas II B Pekanbaru. Data was collected using Zung Self-Rating Depression Scale by Zung (1965) and a family support questionnaire. Both questionnaires were modified and tested for validity and reliability. Data was analyzed using chi square test. From the result, it can be concluded that there was a relationship between family support and level of depression among adolescents in prison (p value = 0.034 < α 0.05). Based on this study, it is suggested to the families to provide high social support to adolescents in prison, so that they can survive or adapt to the needs and experience during their training in prison, rediscover their confidence, and could be a part of community members when they are free.   Keywords              : Adolescent, family support, level of depression, prison. References            : 86 (2000-2015)